ҲОЗИРГИ ЗАМОН ИНГЛИЗ ВА ЎЗБЕК ТИЛЛАРИДА МАҚОЛ ВА МАТАЛЛАРНИНГ ЛИНГВО-КОГНИТИВ АСОСЛАРИ ВА УЛАРНИНГ СТРУКТУРАЛ-СЕМАНТИК ЖИҲАТЛАРИ (Scientific journal of the Fergana State University, 2023)
The article is devoted to analyses of semantic-structural features of proverbs and sayings in modern Uzbek and English languages. Moreover comparative typology and lingua-cognitive aspects of proverbs and sayings are mentioned.